A Tipping Point for "Totally Evidenced Policing": Ten Ideas for Building an Evidence-Based Police Agency. (March 2015) - Sherman, Lawrence W.
Increasing numbers of police professionals have decided to practice evidence-based policing. Yet many of these "early adopters" encounter opposition from their colleagues. Advocates of evidence-based policing (EBP) increasingly ask whether, or how, an entire agency can be transformed at about the same time, rapidly creating a "tipping point" for "totally evidenced" policing—defined as a steady growth of evidence-based decisionmaking on as many practices as possible. Such tipping points may require (1) a powerful advocate for EBP; (2) an "evolutionary" dimension to add on to any "smothering paradigm" that resists the addition of evidence to decision-making; and (3) strong external demands for change. Several attempts to create "totally-evidenced" decisions across entire agencies are under way. This article describes a hypothesis for how they might succeed, consisting of a 10-point plan to be implemented simultaneously.